Bioequivalence study of ipratropium bromide inhalation aerosol using PBPK modelling - Zhang, Jisheng; Wu, Keheng; Liu, Bo; Hou, Shuguang; Li, Xue; Ye, Xiang; Liu, Jack; He, Qing (Frontiers in Medicine, 2023)
Aims: Systemic pharmacokinetic (PK) studies can reflect the overall exposure of orally inhaled drug Products (OIDPs) in the blood after inhalation into the lung and can be used to evaluate the bioequivalence of test and reference products. The aim of this article is: (1) to study the PK characteristics and bioequivalence of ipratropium bromide (IB) inhalation aerosol, reference and test products in healthy Chinese subjects; (2) to establish a physiologically based pharmacokinetic (PBPK) model and verify the accuracy of the model in predicting bioequivalence; (3) attempt to use the model to predict the regional distribution of particles in the lung after inhalation, and discuss the effect of gastrointestinal drug absorption of IB on systemic exposure. Methods: The study involved two clinical studies. Clinical study-1 (registration number: CTR20201284) was used, with non-clinical data to construct and validate a PBPK model in the B2O simulator, a web-based platform for virtual drug development platform. This model assessed different test and reference products’ bioequivalence. Results were compared to a second clinical study (Clinical study- 2: registration number CTR20202291). The particles’ regional distribution in the lung and the gastrointestinal absorption effect on systemic exposure were discussed based on the simulation results. Results: The established PBPK model successfully simulated the in vivo PK characteristics of IB inhalation aerosol, with r2 close to 1. Gastrointestinal absorption had a negligible effect on systemic exposure. Particles accumulated in the alveolar area were cleared within an hour, followed by particles in the bronchioles and bronchi. Conclusions: This model provided a reliable method for exploring the correlation between in vitro and in vivo PK studies of IB inhalation aerosols. According to the simulation results, the test and reference products were bioequivalent.